2021
DOI: 10.1002/gps.5630
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness in older adult mental health services during the COVID‐19 pandemic and before: Associations with disability, functioning and pharmacotherapy

Abstract: Objectives Loneliness is associated with psychiatric morbidity. Restrictions placed on the population during the first COVID‐19 lockdown may have disproportionately affected older adults, possibly through increasing loneliness. We sought to investigate this by examining loneliness in referrals to mental health of older adults (MHOA) services during the first UK COVID‐19 lockdown. Methods Referrals to MHOA services from a large South London catchment area were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 43 publications
(65 reference statements)
2
23
0
Order By: Relevance
“…The strong association between loneliness and both physical and mental health functioning was also particularly important. This aligns with pre-pandemic evidence showing social support being associated with decreased all-cause mortality, cardiovascular disease, depression, and anxiety ( Leigh-Hunt et al, 2017 ), and pandemic-specific research showing loneliness as a strong predictor of worse functioning, affective illness, and non-accidental self-injury ( Greig et al, 2022 ). As loneliness can lead to worse outcomes, effective interventions that are also consistent with COVID-19 infection control and social distancing measures, such as those suggested in the systematic review by Williams et al (2021) , may be of particular importance in veteran treatment.…”
Section: Discussionsupporting
confidence: 78%
“…The strong association between loneliness and both physical and mental health functioning was also particularly important. This aligns with pre-pandemic evidence showing social support being associated with decreased all-cause mortality, cardiovascular disease, depression, and anxiety ( Leigh-Hunt et al, 2017 ), and pandemic-specific research showing loneliness as a strong predictor of worse functioning, affective illness, and non-accidental self-injury ( Greig et al, 2022 ). As loneliness can lead to worse outcomes, effective interventions that are also consistent with COVID-19 infection control and social distancing measures, such as those suggested in the systematic review by Williams et al (2021) , may be of particular importance in veteran treatment.…”
Section: Discussionsupporting
confidence: 78%
“…The COVID‐19 pandemic has the potential to enhance this negative “feedback loop” since it reinforces withdrawal and distancing. This is especially true for individuals with limited health since they might lack strategies or opportunities for compensation (Greig et al, 2021 ). The ELT (Cacioppo & Cacioppo, 2018 ) can further explain the mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study systemtatically reviewed 57 studies from 113 countries or territories and reported a 21% to 24% of prevalence of loneliness in older adults, which was approximately 10 times that in young adults [9]. Increasing evidence indicates that the onset of the COVID-19 pandemic, along with the constainment measures -such as social distancing restrictions; the 'stay at home' order; and the closure of cafes, restaurants, and gyms -have disproportionately affected older adults, increasing the incidence of loneliness [10]. Loneliness is influenced by external circumstances (for example, bereavement and migration) and the human characteristics of the individual such as health status and personality [11].…”
Section: Introductionmentioning
confidence: 99%